Analysis of Heat Transfer and Efficiency of Rack Type Flash Dryer Machine in Purple Sweet Potato Drying Process - Nurwahyuningsih Nurwahyuningsih; Putu Tessa Fadhila; Ade Galuh Rahmadevi; Adi Sucipto; Ahmad Haris Hasanuddin Slamet (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2023)
Purple sweet potato (Ipomoea batatas var Ayumurasaki) has deep purple flesh and tuber skin. The variety of processed purple sweet potato products is increasingly diverse as purple sweet potato production increases, such as cookies and chips. Therefore, a process is needed to turn purple sweet potato into flour before being made into a variety of processed products, namely the drying process. Drying is a process of reducing the water content of a material to a certain level. To determine how much fuel is used by dryer machine, it is necessary to evaluate the effectiveness of the machine. So that in this study the aims were to determine the amount of energy needed to dry purple sweet potatoes, calculate the efficiency of the flash dryer machine and find out the temperature distribution on each tray of the drying machine. Based on the research results of the rack-type flash dryer drying machine, it can be concluded that the mechanism of the heat transfer rate in the purple sweet potato drying process occurs by forced convection heat transfer from the drying air to the purple sweet potatoes and a mass flow rate value of 0.1272 kg/s is obtained, the convection transfer rate in the drying chamber is 836.84 W and the sensible heat value is 1033.84 W. Hence, the amount of heat to dry 3 kg of purple sweet potato for 4 hours is 1870.68 W and an efficiency value of 55.26% is obtained. The total energy required to dry 3 kg of purple sweet potato in 4 hours is 5712.86 kJ.